"IF YOU DON'T KNOW ME BY NOW…": Assessing Race Mismatch through Differences in Race Reports of Fathers in the Fragile Families Survey. (12th April 2021) - Whitehead, Ellen M.; Farrell, Allan; Bratter, Jenifer L.
ABSTRACT: The racial composition of couples is a salient indicator of race's impact on mate selection, but how well do those in intimate partnerships know the racial identities of their partners? While prior research has revealed that an individual's race may be perceived differently than how they identify, most of what is known comes from brief interactions, with less information on established relationships. This study examines whether discrepancies in the reports of a person's race or ethnicity can be identified even within intimate relationships, as well as which relational, social, and attitudinal factors are predictive of divergent or concordant reports. We draw on the Fragile Families and Child Wellbeing Study (n=3467), a U.S.-based dataset that uniquely provides both the father's self-reported race and Hispanic origin and the mother's report of the father's race and ethnicity. We compare reports of the father's race/Hispanic origin from both parents to assess the extent of mismatch, and we distinguish between whether mothers view the father's race as similar to or different from her own. We find roughly 14% of mothers provide a race and Hispanic origin that is inconsistent with the father's report, with a large share reflecting differences in the self-identified and perceived race of fathers who are reported as Hispanic. Among mismatched reports, mothers are more likely to report a race/ethnicity for the father that matches her own, depressing the number reporting interracial unions. Perceptions of racial homogamy are especially likely when mothers view racial sameness as important to marriage. Further, mismatches are more common in the midst of weak relational ties (i.e. non-marital relationships) and are less common when both parents are college-educated. These findings reveal that intimate unions are a site where race is socially constructed and provide insight into how norms of endogamy manifest within formed relationships.